2006
DOI: 10.1111/j.1574-6968.2006.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the carboxy-terminal region of the outer membrane protein AatA in the export of dispersin from enteroaggregative Escherichia coli

Abstract: Enteroaggregative Escherichia coli (EAEC) is an emerging enteric pathogen in both developing and industrialized countries. AatA, an outer-membrane protein that is a homolog of E. coli TolC, facilitates the export of the dispersin protein Aap across the outer membrane in EAEC. To identify which amino acids are important for this export activity, site-directed mutagenesis of the carboxy terminus was performed. An insertional mutant of aatA was complemented with each of several deletion mutants, and was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These equatorial domain mutations affected function without affecting stability or folding of TolC, as shown by cross-linking and immunoblotting. Evidence for the significance of the equatorial domain has also been found in the OMF AatA, where positions F381, L382 and L383 have been shown as essential for Aap secretion ( Iwashita et al, 2006 ). These positions mapped to the equatorial domain as based on the homology model of AatA ( Nishi et al, 2003 ).…”
Section: Functional and Biophysical Evidence Supporting Different Modmentioning
confidence: 93%
“…These equatorial domain mutations affected function without affecting stability or folding of TolC, as shown by cross-linking and immunoblotting. Evidence for the significance of the equatorial domain has also been found in the OMF AatA, where positions F381, L382 and L383 have been shown as essential for Aap secretion ( Iwashita et al, 2006 ). These positions mapped to the equatorial domain as based on the homology model of AatA ( Nishi et al, 2003 ).…”
Section: Functional and Biophysical Evidence Supporting Different Modmentioning
confidence: 93%
“…It is highly likely that AatA and TolC share a common ancestry and similar three-dimensional structures. We demonstrated that the three nonpolar amino acid residues 381 to 383 in the carboxy terminus of AatA are important for Aap secretion activity (12), as the nonpolar amino acid residue 412 (leucine) at the carboxy terminus of TolC is required to express its activity (43). Thus, AatA was found to be a homolog of TolC in EAEC 042.…”
mentioning
confidence: 85%
“…Aap secretion was evaluated as previously described (12,24,33). In brief, strains were grown overnight in high-glucose DMEM.…”
Section: Construction Of a Deletion Mutation At Amino Acid Residue 41mentioning
confidence: 99%
“… 651 Similarly, residues located at the base of carboxy-terminal elongation in the equatorial domain of AatA, homologous to E. coli TolC in enteroaggregative Escherichia coli , are required for the export of its substrate, Aap. 654 Finally, the inability for TolC to form a functional complex with CusAB and to confer resistance to copper and silver ions in vivo was also suggested to be caused by the seemingly different equatorial domains of CusC and TolC. 648 In VceC, part of the loop is not visible in the crystallographic structure probably because of its great flexibility.…”
Section: Outer Membrane Factors (Omfs): Tolc and Othersmentioning
confidence: 99%
“…As will be discussed in more detail below, proposed models of assembly between TolC and AcrA show that this loop is involved in the recruitment and interaction of the OMF porin with its PAP. , The importance of the equatorial domain has been shown by loss-of-function mutants of TolC. It was shown that TolC requires a leucine residue at position 412, located in an equatorial domain that protrudes from the main body of TolC into the periplasm, to be functional . Similarly, residues located at the base of carboxy-terminal elongation in the equatorial domain of AatA, homologous to E. coli TolC in enteroaggregative Escherichia coli , are required for the export of its substrate, Aap . Finally, the inability for TolC to form a functional complex with CusAB and to confer resistance to copper and silver ions in vivo was also suggested to be caused by the seemingly different equatorial domains of CusC and TolC .…”
Section: Outer Membrane Factors (Omfs): Tolc and Othersmentioning
confidence: 99%